⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ x + y + z = 6 7 0 x + y + z = 9 4 0 x + y + z = 5 4 4
Find the value of x + y + z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This solution requires the assumption of integers (which I have just removed from the problem). Furthermore, this solution doesn't prove that we have a unique answer, but that this is the "smallest" answer that we can find.
In fact, if all that we know is that these values are non-negative (because of the square roots), we can still arrive at this unique answer. Do you know how to show this?
@Moderator Why is this the "smallest" answer we can find?
Log in to reply
Because in the solution, all that it establishes is
c
2
−
c
−
2
7
0
≥
0
(and likewise other similar inequalities).
It then uses the (non-ideal) assumption that
a
,
b
,
c
are integers, to arrive at the solution set.
Because the smallest of c which c(c-1) bigger than 270 and have consecutive mutiplier number of a
Problem Loading...
Note Loading...
Set Loading...
⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ x + y + z = 6 7 0 x + y + z = 9 4 0 x + y + z = 5 4 4
Each of the equations have one term involving square root on LHS and rest all including RHS are integers The equations clearly imply that all of x,y,z are perfect squares .
Let ⎩ ⎪ ⎨ ⎪ ⎧ x = a 2 y = b 2 where a,b,c ∈ N z = c 2
The modified equations are :
⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ a 2 + b 2 + c = 6 7 0 a 2 + b + c 2 = 9 4 0 a + b 2 + c 2 = 5 4 4
Now we subtract the equations to derive
a ( a − 1 ) − c ( c − 1 ) = 6 7 0 − 5 4 4 = 1 2 6
a ( a − 1 ) − b ( b − 1 ) = 9 4 0 − 5 4 4 = 3 9 6
c ( c − 1 ) − b ( b − 1 ) = 9 4 0 − 6 7 0 = 2 7 0
We note that : a ( a − 1 ) > c ( c − 1 ) > b ( b − 1 )
From c ( c − 1 ) = b ( b − 1 ) + 2 7 0 we conclude that c ( c − 1 ) > 2 7 0
c ( c − 1 ) > 2 7 0 ⟹ c 2 − c − 2 7 0 > 0
On solving we get c ≥ 1 7 & checking for first few values of c as smallest c is 17 we get
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ c = 1 7 ⟹ a ( a − 1 ) = 1 2 6 + 1 7 . 1 6 = 3 9 8 Not of the form a(a-1) ⟹ rejected c = 1 8 ⟹ a ( a − 1 ) = 1 2 6 + 1 8 . 1 7 = 4 3 2 Not of the form a(a-1) ⟹ rejected c = 1 9 ⟹ a ( a − 1 ) = 1 2 6 + 1 9 . 1 8 = 4 6 8 Not of the form a(a-1) ⟹ rejected c = 2 0 ⟹ a ( a − 1 ) = 1 2 6 + 2 0 . 1 9 = 5 0 6 = 2 3 . 2 2 ⟹ Selected
Solving c=17 we get the other values as follows :
c = 2 0 ⟹ z = c 2 = 4 0 0
a = 2 3 ⟹ x = a 2 = 5 2 9
b = 1 1 ⟹ y = b 2 = 1 2 1
Finally we get x + y + z = 1 0 5 0